The Psychological Impact of COVID-19 Pandemic on Mental Health of Iranian Population. - Mohammadi, Seyede Momeneh; Ashtari, Sara; Fetrat, Masoum Khosh (International Journal of Travel Medicine & Global Health)
Introduction: As the coronavirus disease 2019 (COVID-19) pandemic rapidly sweeps across the world, it is inducing a considerable degree of psychological problems, which can affect everyone in the community. This study aimed to compare the severity of the psychological distress in the general population and patients during the COVID-19 epidemic in an Iranian population.// Methods: In this cross-sectional study, the mental health status of 221 COVID-19 infected patients and 241 participants from general population were investigated by the self-report questionnaire of Depression, Anxiety, and Stress Scale (DASS). The DASS-21 questionnaire and sociodemographic data sheet were filled out by the participants. All statistical analyses were performed using SPSS software version 21. Results: The results indicated higher scores of DASS in patients than the population simultaneously (Wilks Lambda = 0.934, F (3,440) = 10.44, P < 0.001) and individually (Mean difference [MD] = 2.55, 95% CI = 1.48 to 3.62 for depression, MD = 1.48, 95% CI = 0.39 to 2.57 for anxiety, and MD = 1.41, 95% CI = 0.32 to 2.49 for depression score). Conclusion: The present study revealed a high prevalence of mental health problems among patients with COVID-19 and gaps in providing them with mental health services. We call for systematic screening of mental health status for all patients and developing specific psychological interventions for this vulnerable population. Psychosocial assessment and monitoring should be developed in the community to support aspects of COVID-19.